Experience Report of Monitoring on Experimental Analysis of Behavior: Alternative Protocol of Practical Classes - Gotti, Eduardo Sousa; de Oliveira, Elimar Adriana; Neto, Djalma Araújo Guimarães; da Cunha, Cristine Daher Sallum; Formaji, Larissa da Costa (Perspectivas em Análise do Comportamento, 2019)
The present work aims to report on the monitoring activities on the Experimental Analysis of Behavior subject of the Psychology course at the Federal University of the Triângulo Mineiro (UFTM), highlighting the challenges and implications of monitoring in the construction of behavioral repertoires for the teaching of Experimental Analysis of Behavior. The monitoring program is a tool adopted by higher education institutions with different objectives, according to each institution’s monitoring regulations. Experimental Analysis of Behavior has been viewed as a ramification of Behavior Analysis, with theoretical assumptions in Radical Behaviorism, a philosophy that attributes behavioral causality to interactions in the environment.